Plastic stress intensity factor behavior at small and large scale yielding (Fracture and Structural Integrity, 2020)
In this paper the plastic stress intensity factor (SIF) is used to study the coupling effects of loading biaxiality, material properties and cracked body configuration in both the small- and large-scale yielding ranges. A finite element (FE) analysis is performed for a cracked Mode I plane strain plate subjected to biaxial tension/compression loading. The governing parameter of the elastic–plastic crack-tip stress field In factor at the crack tip, J-integral, and the plastic SIF, are calculated as a functions of loading biaxiality and applied stress levels. Special emphasis is put on the behavior of J-integral and the plastic SIF for specified test specimen geometries under mixed mode loading. Finally, the applicability of the plastic SIF approach to large-scale yielding analysis is also discussed.
Keywords: Biaxial loading; J-integral; Plastic stress intensity factor; Mixed mode loading